Software Design of Secondary Programmable and Debugging Development for Converter - 罗凌波; 戴计生; 尚敬 (Kongzhi Yu Xinxi Jishu)
Customers’ ability in secondary programmable and debugging development plays an important role in converter industry with requirements of lower cost and celerity. It proposed a secondary development software CSR_Drive for converter, described its structure, model function and system features, and presented an application example. The detailed design process was described including parameter management, functional connectivity, online monitoring, main-circuit state machine, program updating and system security. Actual operation results show that the proposed software is powerful, stable and reliable.